RANGING THE KHABAROVSK KRAY TERRITORIES BY THE LEVELS OF DYSENTERY EPIDEMIC MANIFESTATIONS - T. A. Zaitseva; O. E. Trotsenko; S. V. Balakhonov; Y. A. Garbuz; T. V. Korita; A. P. Bondarenko; T. N. Karavyanskaya (Acta Biomedica Scientifica, 2017)
Aim: to reveal the Khabarovsk region territories that are under high risk of spread of dysentery in the period of large-scale flood fallout liquidation. Materials and methods. There was the analysis conducted of dysentery incidence during the period of 2003-2012 including distribution of annual and long-term annual average indicators per 100 000 inhabitants throughout administrative entities of Khabarovsk territory. We used methods that reveal tendencies and evaluated dynamic rates of dysentery epidemic process in time. Results and discussion. Khabarovsk region shows uneven levels of manifestations of epidemic process of dysentery not only during evaluation of annual incidence but also among certain administrative territories. During ten years preceding the flood in the Amur River region, long-term annual average level of incidence equaled to 42.7 ± 1.740/0000 The epidemic process was most intense in the Nanayi region, in other six administrative regions long-term annual average levels of incidence were exceeding similar averaged levels in Khabarovsk region. An intense epidemiologic situation on dysentery in several territories of the region was associated with registration of foci of clustered incidence caused by dysentery Sonne of alimentary and water-borne origin including atypical variants of Shigella Sonne. Conclusion. A year before the flood the elevation of dysentery incidence was registered in most of the territories of Khabarovsk Kray, and there was the evidence of outlined tendency of activation of epidemic process. This served as a basis for required adequate emergency measures for prophylaxis of dysentery.